دراســـة نوعيـــة ميـــاه هـــور الحمـــار في جنـــوب العــــراق - زيـــدون ناجـــي عبـــودي (Journal of Engineering and Sustainable Development, 2008)
Some properties were studied for the water of Hammar marsh in the south of Iraq, and the study was performed over a period of four months, months of January, February, and months of June, and July of the year 2006. The measured characteristics are temperature, pH, dissolved oxygen, total dissolved salts, electrical conductivity, chloride, sulfate, and the total hardness. It has been observed that the minimum temperature recorded in the Marsh within the study period is (10.5 oC) while the maximum temperature is (32.5 oC). The results of tests with a pH of the water show that the predominance in the Marsh is alkalinity, as confirmed by previous studies. The analysis of dissolved oxygen concentration records revealed that most areas of the Marsh are of good ventilation, while some sites have very low ventilation, below the critical limit. The minimum and maximum values of the concentration of dissolved oxygen in the marsh are (2.0 and 12.3 mg/L), respectively. Moreover, a considerable variation in the concentration of total dissolved salts was recorded, where the minimum value is (1000 mg/L), and the maximum value is (11500 mg/L). The maximum and the minimum values of electrical conductivity are (2.2 and 10.5 mS/cm), respectively. These values were faller in the range of the results introduced by related previous studies on the Marsh and water bodies. The same thing was held for chloride, sulfate, and total hardness. Their averages are much more than the values in the Euphrates River before entry into the marshes